Outcome of conventional and alternative assessment during online teaching and learning mode between open book and recall test - Ismail, Soraya; Mohd Zainudin, Maizura; Hamzah, Hairul Aini; Abdul Rahim, Roslina; Khaing, Aye Thi; Wahid, Hanan Hamimi; Mohd Radzuan, Hazulin; Ismawi, Hidayatul Radziah; Ahmad Affandi, Khairunisa; Mat Harun, Noraihan; Mohamed Bakrim, Norbaiyah; Abd. Rahim, Nour El Huda; et al. (2020)
The COVID-19 pandemic has resulted in lockdown of many universities throughout the world. Malaysia too was not spared from the lockdown which is locally known as the ‘movement control order’ (MCO). This situation forced both educators and students to shift towards online teaching and learning using digital platform. Prior to the lockdown, conventional face-to-face teaching and learning was commonly practiced along with recall exam-oriented assessment for first year medical students. With the abrupt change, many challenges were faced especially in assessing first year medical students. Our study aimed to compare the outcome of assessment during face-to-face teaching and online teaching between open book assessment and recall tests. The alternative online assessment was conducted amongst all first-year medical students (n=143) in Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia during the MCO. This cohort of students experienced both face-to-face and online teaching and learning. The assessment data was retrieved from the academic office, Kulliyyah of Medicine. The conventional assessment method was 100% recall test comprised of multiple-choice questions (MCQ), short notes, modified essay question (MEQ) and objective structured practical examination (OSPE). Meanwhile, the alternative online assessment methods were i) open book assignment comprised of MEQ and MCQ and ii) synchronized online MCQ recall test. The mean grade for conventional recall test assessment method was 60% with the minimum and maximum grades of 29% and 79% respectively. For the alternative online assessment recall test, the mean grade was 58% with the minimum and maximum grades of 14% and 78% respectively. For the alternative online assessment open book assignment, the mean grade was 77% with the minimum and maximum grade of 32% and 92% respectively. For the open book assignment, the mode (80%) and median (78%) were higher than the mean (77%). The grades obtained by students during conventional and online assessment recall tests were comparable. Though the average grades were higher for online open book assessment, the pattern of distribution was similar in both recall and open book assessment methods. The online assessment method carried out here was able to discriminate between the good, moderate and weak students’ performance.